2017
DOI: 10.56093/ijas.v87i4.69443
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, character association and path coefficient analysis in China aster (Callistephus chinensis)

Abstract: Ten cultivars of China aster [Callistephus chinensis (L.) Nees] were evaluated for 12 growth and flowering related traits to study their genetic parameters such as variability, heritability, genetic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), correlation and path coefficient analysis. Significant differences among cultivars for all the growth and flowering related traits were reported through analysis of variance. Wide range in mean performance has been reported in characters suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
4
0
0
Order By: Relevance
“…At the same time, traits like days to fifty percent flowering and days to first harvest recorded the highest negative correlation with many traits. The results align with Teerath et al (2017) [26] , who observed similar results in China aster. Kumar et al (2019) [14] in Marigold stated that flower yield per hectare positively correlated with plant height, plant spread, dry weight of flower, number of flowers per plant, flower diameter and flower yield per plant.…”
Section: Correlationsupporting
confidence: 92%
“…At the same time, traits like days to fifty percent flowering and days to first harvest recorded the highest negative correlation with many traits. The results align with Teerath et al (2017) [26] , who observed similar results in China aster. Kumar et al (2019) [14] in Marigold stated that flower yield per hectare positively correlated with plant height, plant spread, dry weight of flower, number of flowers per plant, flower diameter and flower yield per plant.…”
Section: Correlationsupporting
confidence: 92%
“…These ndings were indicating the presence of differences among the all traits with respect to genetic advance. Similar ndings were reported by Rai et al (2017) in China aster and Yuvraj and Dhatt (2014) in marigold.…”
Section: Genetic Advancesupporting
confidence: 89%
“…The phenotypic coe cient of variation (PCV) was greater than genotypic coe cient variation (GCV) among the all characters it was might be due to environmental in uence. These results were conjunction with the ndings of Rai et al (2017) studies in China aster.…”
Section: Coe Cient Of Variation (%)supporting
confidence: 83%
“…Higher For flower diameter, PCV estimates was found to be high (20.02%), and a moderate GCV (18.51%), while, days to optimum flowering (17.04% and 15.02%) and flowering duration (18.27% and 16.41%) showed moderate estimates of PCV and GCV, respectively. Similar results of higher estimates of PCV and GCV were reported in chrysanthemum (Telem et al, 2017 andHenny et al, 2021), gaillardia (Arulmani et al, 2015) and China aster (Rai et al, 2017, Bhargav et al, 2019and Nataraj et al, 2021.…”
Section: Estimation Of Genetic Parameters For Growth and Flowering Tr...supporting
confidence: 65%